2017
DOI: 10.1136/bmjopen-2016-014920
|View full text |Cite
|
Sign up to set email alerts
|

How are age-related differences in sleep quality associated with health outcomes? An epidemiological investigation in a UK cohort of 2406 adults

Abstract: ObjectivesTo examine age-related differences in self-reported sleep quality and their associations with health outcomes across four domains: physical health, cognitive health, mental health and neural health.SettingCambridge Centre for Ageing and Neuroscience (Cam-CAN) is a cohort study in East Anglia/England, which collected self-reported health and lifestyle questions as well as a range of objective measures from healthy adults.Participants2406 healthy adults (age 18–98) answered questions about their sleep … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
122
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(138 citation statements)
references
References 89 publications
10
122
5
1
Order By: Relevance
“…No significant age-interactions were found for any of the sleep items. Thus, the UKB results were in agreement with the lack of meaningful cross-sectional sleep-hippocampal volume relationships in Lifebrain, and aligns with previous findings within a Lifebrain cohort (Cam-CAN) which found no cross-sectional associations between PSQI subcomponents and white matter microstructure (indexed by Fractional anisotropy) across ten tracts [58].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…No significant age-interactions were found for any of the sleep items. Thus, the UKB results were in agreement with the lack of meaningful cross-sectional sleep-hippocampal volume relationships in Lifebrain, and aligns with previous findings within a Lifebrain cohort (Cam-CAN) which found no cross-sectional associations between PSQI subcomponents and white matter microstructure (indexed by Fractional anisotropy) across ten tracts [58].…”
Section: Resultssupporting
confidence: 89%
“…Whereas sleep duration, efficiency and problems were worse with higher age in Lifebrain, self-reported sleep quality was better with age, and sleep latency and daytime tiredness showed improvement until middle age or longer. The global PSQI score showed little change before 50 years of age, after which worse scores were seen for the rest of the age-span, suggesting PSQI sum score may not be the best measure to use in lifespan cohorts [58]. These patterns fit well with the results from a meta-analysis of polysomnography data [2].…”
Section: Discussionmentioning
confidence: 61%
“…Among them, only sleep efficiency has been indicated to continuously decline in older age (>60 years; Ohayon et al., ). Clustering of poor sleepers has shown that inefficient sleepers are mostly elderly people (Gadie, Shafto, Leng, Cam‐Can, & Kievit, ). Therefore, negative health consequences of low sleep efficiency that covary with ageing in later life require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The Karolinska Sleep Questionnaire (KSQ) 46,47 was used for Betula and converted to PSQI (SI and 35 ). Although lifespan changes in sleep are pronounced 35,48 , mean changes as well as individual differences in change over a few years are rather small 17,49 and considered as negligible here. If multiple observations were available, the mean value was used.…”
Section: Methodsmentioning
confidence: 97%